Is There a Role for Placental Cultures in Cases of Clinical Chorioamnionitis Complicating Preterm Premature Rupture of Membranes? - Fouks, Yuval; Many, Ariel; Orbach, Rotem; Shapira, Udi; Amit, Sharon; Grisaru-Soen, Galia; Mandel, Dror; Shinar, Shiri (American Journal of Perinatology, 2017)
Objective To assess the role of placental cultures in cases of preterm premature rupture of membranes (PPROM) complicated by chorioamnionitis and to determine the effect of positive cultures on short-term neonatal outcomes.Design A retrospective single-center study. The medical records of all women with PPROM between January 1, 2011, and December 31, 2015, were reviewed. Cases were divided into placental culture positive (group A) and placental culture negative (group B) groups. Maternal and pregnancy characteristics as well as short-term neonatal outcomes were compared between groups.Results During the 5-year study period, 61 cases of clinical chorioamnionitis complicating PPROM were diagnosed: 25 cases were culture positive (group A) and 36 were culture negative (group B). Neonatal outcome measures, including Apgar score at 5 minutes (p = 0.028; odds ratio [OR]: 5.27; confidence interval [CI]: 1.19–23.34), respiratory distress syndrome (p = 0.026; OR: 4.11; CI: 1.18–14.25), and neonatal infection (p < 0.0001; OR: 11.59; CI: 3.37–39.87) were significantly more common in group A newborns, regardless of gestational age at delivery as was the composite neonatal outcome (p = 0.017; OR: 7.35: CI: 1.42–37.79). Placental isolates were primarily Streptococci and Escherichia coli.Conclusion Placental cultures may be an essential predictor of neonatal morbidity in PPROM and may contribute to the modification of neonatal treatment.
Keywords: placental cultures; preterm premature rupture of membranes; chorioamnionitis; neonatal outcome; antibiotics